2004
DOI: 10.1021/bc0498976
|View full text |Cite
|
Sign up to set email alerts
|

Cyclen-Based Phenylboronate Ligands and Their Eu3+ Complexes for Sensing Glucose by MRI

Abstract: Novel cyclen-based phenylboronate ligands and their corresponding Eu(3+) complexes have been examined as glucose sensors using chemical exchange saturation transfer (CEST) MR imaging for detection. Two isomeric bis-phenylboronate complexes, Eu(4) and Eu(10), and a mono-phenylboronate complex, Eu(12), had been prepared and characterized by UV and circular dichroism spectroscopy, mass spectrometry, and CEST imaging. Both the free ligands and their Eu(3+) complexes bind to simple sugars, but their selectivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 53 publications
0
67
0
Order By: Relevance
“…This single pool ratiometric approach has shown that it is possible to determine glucose concentration in the physiologically relevant range (~5 mM) for imaging systems. 24 Of course glucose is not the only sugar that contains a cis-diol; however, experiments with other sugars, such as fructose and galactose, showed that EuDTMA-2PB 3+ has a strong preference for glucose over these other sugars, and since the physiological concentrations of these other sugars are normally much lower than that of glucose, they are not anticipated to prevent the use of this complex in vivo.Although the experiment has not yet been performed, it is easy to see from the spectra shown ( Fig. 7) how this single-pool ratiometric approach could also be applied to the measurement of temperature and, in principle, any of the other responsive PARACEST agents discussed here, such as a recently reported sensor for the biologically important Zn 2+ ion.…”
mentioning
confidence: 99%
“…This single pool ratiometric approach has shown that it is possible to determine glucose concentration in the physiologically relevant range (~5 mM) for imaging systems. 24 Of course glucose is not the only sugar that contains a cis-diol; however, experiments with other sugars, such as fructose and galactose, showed that EuDTMA-2PB 3+ has a strong preference for glucose over these other sugars, and since the physiological concentrations of these other sugars are normally much lower than that of glucose, they are not anticipated to prevent the use of this complex in vivo.Although the experiment has not yet been performed, it is easy to see from the spectra shown ( Fig. 7) how this single-pool ratiometric approach could also be applied to the measurement of temperature and, in principle, any of the other responsive PARACEST agents discussed here, such as a recently reported sensor for the biologically important Zn 2+ ion.…”
mentioning
confidence: 99%
“…The distance between the pendant boronate arms appears to be an important factor in determining the affinities for the various saccharides. The 1,7-disubstituted derivative 38 (Eu-DOTAM-2M-2PB; FiguRe 19) had a high and selective binding affinity for glucose (apparent stability constant of the resulting boronate ester: 339 ± 29 M -1 at pH 7) [64,65]. The glucose is bound to the complex in a 1:1 fashion by forming a bridge above the Eu(III)-bound water molecule (FiguRe 19).…”
mentioning
confidence: 99%
“…Since the plasma concentration of this material is normally relatively low, this should not interfere with the use of the complex as a glucose sensor. On the other hand, the good affinity for glycated HSA allows the in vitro determination of the degree of glycation in serum, using MRI and high-throughput methods [65].…”
mentioning
confidence: 99%
“…For example, some bioactivated MRI contrast agents, whose ability to relax water protons is greatly enhanced by recognition of a biomolecule, have been reported for monitoring of enzyme activity, Ca 2ϩ , pH, p(O 2 ), etc. [11][12][13][14][15] These MRI contrast agents induce a change in the water proton relaxation time (T 1 or T 2 ) in response to the presence of the target biomolecule.…”
Section: ؉ )-Based Mri Contrast Agents For Bioimagingmentioning
confidence: 99%